ANALYSIS OF FACTORS INFLUENCING THE LEVEL OF ASSET DISCLOSURE IN LOCAL GOVERNMENT FINANCIAL REPORTS IN CENTRAL SULAWESI 2020-2024 - Maulana Indri; Muhammad Din; Muhammad Ilham Pakawaru; Rahma Masdar (JAT : Journal Of Accounting and Tax, 2026)
Study This aim for analyze factors that influence level disclosure asset in Report Finance the Regional Government (LKPD) related to Central Sulawesi Province covers the period from 2020 to 2024. The issue being explored arises from the demand for precise information and the inconsistencies identified in earlier studies. A quantitative method has been utilized, drawing on secondary data sourced from the LKPD and the Audit Report (LHP) compiled by the Supreme Audit Agency (BPK). The study analyzed 65 cases chosen from 12 districts and one city over a span of five years, employing WarpPLS for the analysis. Findings indicate that factors such as the size of the regional government, the region's wealth, fiscal autonomy, auditor assessments, and the intricacy of regional governance have a significant and positive influence on the degree of asset disclosure, whereas the results of audits have a negative and negligible effect. This research suggests that the internal factors within the regional government are more vital for improving asset disclosure transparency than external corrective measures.